Pengaruh Endorphin Massage terhadap Produksi ASI pada Ibu Post Partum di Puskesmas Somba Opu Kabupaten Gowa - Nurfaizah Alza; Nurhidayat Nurhidayat (Jurnal Ilmiah Kesehatan (JIKA), 2020)
Endorphins could create a feeling of comfort and comfort that reduces the anxiety that mothers feel. Back massage is done to stimulate the oxytocin reflex through sensory somatic stimulation of the afferent system. The purpose of this study was to look for the effect of endorphin massage on breast milk production in post partum mothers at the Somba Opu health center in Gowa regency in 2018. This type of research was a quantitative quasy experiment approach. The study was conducted in April until May 2018 in Somba Opu Health Center, Gowa Regency in 2018. The population in this study were all post partum mothers in Somba Opu Health Center in March to April 2018 with a sample of 34 people taking purposive sampling using the test Mann Whitney. The results showed that the number of subjekts based on the ASI production posttreatment group after the endorphine message method showed that the number of subjekts with ASI production was as smooth as many. There is an effect of endorphine message with breast milk production in post partum mothers obtained Z value of -3.178 with p value 0.001 <? 0.05. Post partum mothers have a smooth milk production after endorphin massage is more than those without endorphin massage and there is an effect of endorphine message on breast milk production.